2007
DOI: 10.1093/ndt/gfm799
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular endothelium in kidneys with congenital nephrotic syndrome of the Finnish type (NPHS1)

Abstract: Background. The role of glomerular capillary endothelium in the pathophysiology of nephrotic kidney diseases is poorly known. We analysed the glomerular endothelial lesions in kidneys from patients with congenital nephrotic syndrome of the Finnish type (NPHS1). The disorder is caused by a genetic defect in a major podocyte slit diaphragm protein, nephrin. It manifests as nephrotic syndrome soon after birth and leads to glomerular sclerosis in early childhood. Methods. The glomerular capillary and endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…VEGF-A is increased in congenital nephrotic syndrome of the Finnish type and in acquired glomerular diseases associated with nephrin down-regulation, such as diabetic nephropathy (7,29,30). Our studies also showed that podocyte-specific VEGF 164 gain of function during development causes nephrotic syndrome in mice (31) and in adult mice, leads to proteinuria, podocyte effacement, and loss of slit diaphragms (25).…”
supporting
confidence: 65%
“…VEGF-A is increased in congenital nephrotic syndrome of the Finnish type and in acquired glomerular diseases associated with nephrin down-regulation, such as diabetic nephropathy (7,29,30). Our studies also showed that podocyte-specific VEGF 164 gain of function during development causes nephrotic syndrome in mice (31) and in adult mice, leads to proteinuria, podocyte effacement, and loss of slit diaphragms (25).…”
supporting
confidence: 65%
“…These abnormalities are very similar to those described in nephrin-or podocin-null mice 11,32 and to podocyte and endothelial cell abnormalities described in kidneys from infants with CNSF. 9,33,34 This finding suggests that moderate podocyte VEGF 164 overexpression during organogenesis is sufficient to disrupt the development of mature podocyte foot processes, cell-cell interactions, and glomerular capillaries. VEGF-A is critical for fenestrae development and maintenance in mature glomerular endothelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…8 VEGF is increased in congenital nephrotic syndrome of the Finnish type (CNSF). 9 Nephrin mutations cause CNSF, characterized by massive albuminuria at birth due to severe glomerular filtration barrier abnormalities. 10 Kidneys in CNSF fail to develop slitdiaphragms and podocyte foot processes are flattened and fused, 10,11 whereas associated mesangial expansion, endothelial blebs, and proliferation lead to capillary obliteration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural analysis of the glomerular capillary loops shows complete foot process effacement and swelling of endothelial cells. 11 NPHS1, encoding nephrin, was identified by positional cloning more than a decade ago and is the major gene involved in CNF in Finnish populations (98% of cases). 12 The Fin major (c.121delCT; p.L41fs) and Fin minor (c.3325CϾT; p.R1109X) mutations account for 78 and 16% of the mutated alleles, respectively, in Finnish cases 12 ; however, these mutations are rarely found in other ethnic groups.…”
mentioning
confidence: 99%